Correlations among soil biochemical parameters, crop yield, and soil respiration vary with growth stage and soil depth under fertilization. (21st May 2021) - Liang, Guopeng; Wu, Xueping; Cai, Andong; Dai, Hongcui; Zhou, Liping; Cai, Dianxiong; Houssou, Albert; Gao, Lili; Wang, Bisheng; Li, Shengping; Song, Xiaojun; Wu, Huijun
Abstract: Most studies only measure soil biochemical parameters in the surface soil at one growth stage to uncover how fertilization affects crop yield and soil respiration. A field study was conducted in a wheat ( Triticum aestivum L.)–maize ( Zea mays L.) rotation system to determine whether correlations among soil biochemical parameters, crop yield, and soil respiration vary with growth stage and soil depth. Annual crop yield, seasonal soil respiration, soil biochemical parameters at different growth stages (i.e., soil enzyme activity and available N content), and soil chemical parameters at different soil depths (i.e., soil organic carbon [SOC] and total nitrogen [TN] content) were measured. Stronger positive relationships between crop yield, soil respiration, and soil biochemical parameters were found at the first growth stage relative to other stages during both the 2013 wheat and 2014 maize growing seasons. In addition, the most significant relationship among soil chemical properties, crop yield, and soil respiration was found at 20‐to‐40‐cm soil depth during the 2013 wheat growing season but was found at 0‐to‐20‐cm soil depth during the 2014 maize growing season. Overall, correlations among soil biochemical parameters, crop yield, and soil respiration vary with growth stage and soil depth under fertilization. Our study indicates that single time‐point measurements of only surface soil biochemical parameters are not sufficient to understand fertilization impacts on crop yield and soil respiration. Core Ideas: Correlations among soil biochemical parameters, soil respiration, and yield vary among growth stages. Correlations among soil biochemical parameters, soil respiration, and yield vary among soil depths. Single time‐point measurements of the surface soil biochemical parameters are not sufficient.